Drugs and Philippine Society - Lasco, Gideon (Archīum Ateneo, 2021)
Drugs and Philippine Society is a collection of critical essays that look at drug use; drug wars; and drug policies in the Philippines from different angles; from the perspectives of scholars; social and cultural workers; artists and activists present and past. In doing so; it seeks to uncover societal prejudices about a long- misunderstood subject—and unmask the many contexts of how drugs are used and misused in the country. Aside from a foreword by Sheila Coronel and a critical introduction by Gideon Lasco; the anthology gathers photographs of President Rodrigo Duterte’s war on drugs since 2016 and its effects on Philippine communities to further contextualize the urgent need to rethink drug policies not only in the country but around the world.